2017
DOI: 10.1016/j.anorl.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of glottal insufficiency treated by hyaluronic acid injection: Retrospective 20-case series

Abstract: Hyaluronic acid injection was effective in treating glottal failure, improving objective and subjective vocal parameters, which remained satisfactory even 6 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Glottic insufficiency can impact a patient's quality of life in many ways, including dysphonia, aspiration risks, or airway compromise [24]. VFIs are often used as a safe, temporizing treatment for glottic insufficiency to improve voice outcomes [2][3][4]. Patient satisfaction with VFIs are reflected in the low DRS scores reported in this study; the majority of our patients reported no (61.0%) or mild (24.3%) decisional regret (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Glottic insufficiency can impact a patient's quality of life in many ways, including dysphonia, aspiration risks, or airway compromise [24]. VFIs are often used as a safe, temporizing treatment for glottic insufficiency to improve voice outcomes [2][3][4]. Patient satisfaction with VFIs are reflected in the low DRS scores reported in this study; the majority of our patients reported no (61.0%) or mild (24.3%) decisional regret (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…They were first introduced in 1911 and are now commonly completed as office-based procedures rather than operative procedures requiring general anesthetic [ 1 , 2 ]. While in-office VFIs have high completion rates with minimal complications and improve voice outcomes [ 3 , 4 ], there is a paucity of research on patients’ decision-making process with this treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…Our mean volume of 0.72 mL was similar to the 0.44 to 0.65 mL reported by others for HA VFIs. 24,25 LEVFI does not aim to over-inject and cause a strained voice, which may explain a higher than expected reinjection rate at follow-up. It is difficult for the authors to definitively ascertain if repeat injections were done because of resorption of HA or because patients were under-injected to begin with.…”
Section: Discussionmentioning
confidence: 94%
“…The study concluded that HA injection is an effective treatment for glottal insufficiency, and it can improve both objective and subjective vocal parameters even at the postoperative sixth month. 24 In another study of 50 patients, acoustic analysis and VHI-10 questionnaire results were evaluated after HA injections. The study found a significant improvement in vocal fold functions 4 weeks after the injection laryngoplasty.…”
Section: Discussionmentioning
confidence: 99%